An Italian retrospective multicentric audit on the traceability of Vascular Access Devices procedures - Esposito, Maria Rosaria; Rubbi, Ivan; Costa, Alice; Pasquinelli, Gianandrea; Mongardi, Maria (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Abstract. Background and aim: The traceability of nursing care in clinical documentation is a standard of good practice and provides a remarkable improvement in vascular access devices (VAD) and infusion therapy research. The study aims to describe the traceability of VAD practices in medical records and the level of adherence to EBP practice in vascular access management. Research design and Methods: a multicenter retrospective observational study was conducted in 30 healthcare facilities in 11 Italian Regions by analyzing medical records from medical, surgery, and intensive care units that use VADs for patient care. Results: by analyzing 2813 out of 3047 folders, a lack of documentation on the daily patient care records was found on several items: date of removal 70% (n.3.543); reason of removal 46% (n.2302); date of change dressing 19.9% (n.985); site monitoring/inspection 38.5% (n.1.943); evaluation using scales 12% (n.608) and complications 3% (n.133). Conclusions: Although constituting an integral part of the EBP of good care practice, recording the VAD procedures is still deficient in some areas thus requiring further enhancements. This study represents a contribution to increasing the VAD documentation within organizations using the clinical audit as a review tool among peers.